The Simulation of Heat Propagation Rate in Smart Roasting Process Using Finite Difference Method - Sari, Rafika; Lubis, Nuraina Fika; Fitriyani, Aida; Mayadi, Mayadi (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2020)
In the industrial 4.0 era, there have been many developments in daily equipment that have been transformed into more sophisticated tools both in terms of how they are used, the efficiency of their work and the quality of the results obtained due to the digitization process that is easily accessed by many people. Therefore, As the early step, the paper discusses the computational modeling in the automatic cooking methods, namely the smart roaster system. The cooking method in the form of granules by using a roasting process, which generally utilizes heated sand, is interesting to learn since there are two mechanisms of heat propagation from the pan to the food object, namely the mechanism of heat propagation by conduction and radiation, but in this study, the heat propagation due to temporary convection was ignored. The first mechanism is accommodated by Fourier's Law, while the second is by Stefan-Boltzmann's Law. For simplification, the system is discussed in one dimension with the same grain size, but the object can have a different size. The composition of the pan walls, grains of sand, empty space, and food objects can be randomized so that various configurations can be created. Discussed how the process of heat propagation can occur in the roasting process and also radiation to the surrounding space on the top of the sand surface. The numerical analysis method is used with the finite difference method and the Matlab programming language for simulation.